Mechatronics Design Methodology applied at manufacturing companies. (3rd February 2010) - Guerra-Zubiaga, David A.; Rios, Edgar; Parkin, Robert; Jackson, Mike; Tomovic, Mileta; Ramirez-Mendoza, Ricardo
New mechatronic products require integration of novel methods and tools to be developed. Mechatronics is becoming the basis for high-tech products, such as autonomous systems, high precision processes or adaptive devices. The complexity derived from integrating effectively its components may mislead and produce confusion during its design. This paper presents a new methodology to obtain a mechatronic design and will show some of the available virtual tools to design, evaluate and integrate the different parts of it. The methodology was applied to 40 different mechatronic projects creating good university-manufacturing companies links with satisfactory results.